Fluxo contábil de ativos biológicos: um estudo de caso na Companhia de Alimentos do Nordeste – CIALNE - Viana, Felipe Lima (2020)
The theme of biological assets has proved to be a fertile field for debates in Brazil, due to the importance of agribusiness in the country, as well as the difficulty of its measurement, because they are living beings subject to biological transformations such as growth, procreation, degeneration and death, wich causing them qualitative and quantitative changes. Studies in the area of agribusiness accounting emphasize the recognition, the way of measuring, and the disclosure of biological assets, which makes the study of the applicability of CPCs to the poultry sector, proposed here, holds a potential contribution to the area of accounting knowledge. This study proposes a model of biological assets accounting flow applied to the poultry activity, showing the peculiarities of the productive process. Therefore, the case study was chosen as a methodological procedure, based on three sources of evidence: primary data, extracted from interviews with Company employees and by direct observation; and secondary data, obtained through the examination of financial statements and production reports for the period of 2018. In the characterization of the company chosen for this research, it was found that 97% of its revenue comes from aviculture and that the value of the biological asset Birds corresponds to 63.33% of its total biological assets and 18.45% of the company's assets in the period of study, showing itself to be expressive and confirming the importance of the analysis carried out. From the data obtained, we verified that the company carries out a vertical poultry activity, from poultry to the slaughter and industrialization of broiler chicken and that, in all stages of the production process, the organization consumes a part of its production while another part is sold to the market. The main biological assets and agricultural products identified were: grandparent poultry (growing and producing), poultry (growing and producing), broiler chickens, fertile grandparent eggs, breeding chicks, fertile eggs, and broiler chicks. The main finding of the research is the confirmation of the viability of the biological assets accounting flow model using information about groups of assets, being possible to measure and demonstrate biological changes. The information obtained in the research is of great importance for the decision-making process, allowing a more realistic perception of the entity's assets. The research also contributes to the literature on the accounting flow of biological assets and agricultural products, especially in measuring those that have no market value.